Nutrient cycling at Dois Irmãos forest (Recife, PE, Brazil) through litterfall - Sampaio, Everardo V. S. B.; Nunes, Katia S.; Lemos, Eurico E. P. (Pesquisa Agropecuaria Brasileira, 2014)
The amounts of leaves, twigs, flowers and fruits falling to the ground and their contents of P, K, Ca, Mg, Mn, Fe and Zn, were determined during three years. The material was collected every 14 days from eleven 1 m2 collectors. Every three months samples of young and old leaves from trees around the collectors and samples of the litter above the soil were also gathered and analysed. The amounts of litterfall varied little from year to year, averaging 6.4 t/ha of leaves and 1.7 t/ha of twigs, yearly. Flowers and fruits amounted to only 3% of total litterfall. Leaf fall was mostly from October to January, twig fall from June to July, and flowers and fruits from December to April. Litterlayer on the ground averaged 39 t/ha. There were no significant differences in nutrient contents of all plant parts along the year except for K content, which was 2 to 3 times higher in the dry season than in the wet season. In general, P, K and Mg contents were highest in leaves collected from the trees, decreasing in fallen leaves and decreasing still more in litterlayer and twigs, while the opposite occurred with Ca, Mn, Fe and Zn contents. Through litterfall 49 kg/ha of Ca, 23 of K, 14 of Mg, 3 of P, 1.3 of Fe and 0.4 of Mn and Zn return to the ground yearly. In the litterlayer on the ground there were 3 times more K and 4 to 7 times more of all other nutrients than in annual litterfall.